2004
DOI: 10.1111/j.1523-1755.2004.00652.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of urinary albumin excretion to coronary heart disease and low renal function: Role of blood pressure

Abstract: Results support the use of urinary albumin excretion as marker of CHD and slightly reduced renal function in hypertensives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
(42 reference statements)
1
22
0
Order By: Relevance
“…CHD was analyzed as the most common clinical presentation of vascular disease 11 and defined with use of ECG data combined with symptoms reported in the questionnaire as described previously. 8 Myocardial infarction or ischemia were combined in analysis, because previous data showed that uAE is similarly and independently related to both disorders. 8 Data of skinfold thickness (triceps and subscapular) and weight were used for the estimation of fat mass.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…CHD was analyzed as the most common clinical presentation of vascular disease 11 and defined with use of ECG data combined with symptoms reported in the questionnaire as described previously. 8 Myocardial infarction or ischemia were combined in analysis, because previous data showed that uAE is similarly and independently related to both disorders. 8 Data of skinfold thickness (triceps and subscapular) and weight were used for the estimation of fat mass.…”
Section: Methodsmentioning
confidence: 99%
“…8 Myocardial infarction or ischemia were combined in analysis, because previous data showed that uAE is similarly and independently related to both disorders. 8 Data of skinfold thickness (triceps and subscapular) and weight were used for the estimation of fat mass. 12 Nonfat mass was calculated as weight minus fat mass.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Prevention of Renal and Vascular End-Stage Disease (PREVEND) study conducted in nondiabetic residents of the city of Groningen (the Netherlands), it was observed that GFR estimated by 24-h creatinine clearance tended to be elevated in subjects with high-normal AER (15-30 mg/day), whereas macroalbuminuria was independently associated with a reduction in creatinine clearance below values expected for age and sex (4). In the Gubbio study conducted in a sample of an Italian community of 1,632 subjects aged 45-64 years, no relationship between increasing AER and the prevalence of "low" creatinine clearance (Ͻ60 ml/min) was found (31).…”
Section: Albuminuria and Renal Outcomes In Essentialmentioning
confidence: 99%